Voicing the Voice of Senior Academic Administrators on Education System in Northern Cyprus - Irkad, Ulus (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The purpose of this paper is to introduce the perceptions of senior academic administrators in Northern Cyprus Ministry of Education on the current education system. That is to say the structure of the education system as a whole. In order to carry out this study, 14 senior academic administrators’ point of view has been taken by using semi-structured interviews. There is no doubt that in qualitative research semi-structured interviewing is a flexible and powerful tool to capture the voices and the ways people make meaning of their experiences (Kvale, 2007). This study is a case study. As Yin (2009a:18) stated: “An empirical inquiry about contemporary phenomenon (e.g., “case”), set within its own real-worldcontext – especially when the boundaries between phenomenon and context are not clearly evident”. Therefore, by reflecting upon the current education system in North Cyprus as a ‘case’, the authors tried to show the real context of the education system itself. The data collected from the semi-structured interviews were analyzed by using content analysis. According to the findings of this research study, the current education system must be re-constructed considering the curriculum, strategies in teaching and learning approaches, building up collaborative and student-centered classrooms, applying active learning strategies and voicing the voice of the senior academic administrators during the decision-making process.

ÖZ: Bu çalışmanın amacı, Kuzey Kıbrıs Eğitim Bakanlığı'ndaki üst düzey akademik yöneticilerin mevcut eğitim sistemine ilişkin algılarını ortaya koymaktır. Yani bir bütün olarak eğitim sisteminin yapısı. Bu çalışmanın gerçekleştirilebilmesi için yarı yapılandırılmış görüşmeler kullanılarak 14 üst düzey akademik yöneticinin görüşü alınmıştır. Nitel araştırmalarda yarı yapılandırılmış görüşmenin, sesleri ve insanların deneyimlerini anlamlandırma biçimlerini yakalamak için esnek ve güçlü bir araç olduğuna şüphe yoktur (Kvale, 2007). Bu çalışma bir vaka çalışmasıdır. Yin'in (2009a:18) belirttiği gibi: "Özellikle fenomen ve bağlam arasındaki sınırlar açıkça belli olmadığında, kendi gerçek dünya bağlamı içinde belirlenen çağdaş fenomen (örneğin "vaka") hakkında ampirik bir araştırma. Bu nedenle yazarlar, Kuzey Kıbrıs'taki mevcut eğitim sistemini bir 'vaka' olarak yansıtarak, eğitim sisteminin kendisinin gerçek bağlamını göstermeye çalışmışlardır. Yarı yapılandırılmış görüşmelerden toplanan veriler içerik analizi kullanılarak analiz edilmiştir. Bu araştırma çalışmasının bulgularına göre, mevcut eğitim sisteminin müfredat, öğretme ve öğrenme yaklaşımlarındaki stratejiler, işbirlikli ve öğrenci merkezli sınıflar oluşturma, aktif öğrenme stratejilerinin uygulanması ve kıdemli akademisyenin sesini duyurması dikkate alınarak yeniden yapılandırılması gerekmektedir.
Educational Sciences - Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Education, Dept. of Educational Sciences, 2021. Co-Supervisor: Assoc. Prof. Dr. Hamid Caner and Supervisor: Asst. Prof. Dr. Bengi Sonyel
Keywords: Thesis Tez; Educational Sciences Department; Education--Education System--Education Policy--Cyprus (Turkish Republic of Northern Cyprus, 1983-).; Educational policy--Cyprus, North; Perception; Education System; Ministry of Education Senior Academic Administrators (MESAA); Active Learning; Voice